2022
DOI: 10.1155/2022/4033033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Phospholipid and Cholesterol Levels on Growth, Molting Performance, and Ovary Development in Female Juvenile Crayfish (Procambarus clarkii)

Abstract: The interaction between phospholipid (PL) and cholesterol (CH) on growth performance, molting rate, hepatopancreas fatty acid composition, and ovary development of the female red swamp crayfish (Procambarus clarkii) was investigated. Nine diets containing three PL levels (0, 20, and 60 g/kg) and three CH levels (0, 5, and 10 g/kg) were included in the study. Female crayfish (initial weight: 5.92 ± 0.03 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…The results are different from previous studies, which commonly found that C18:n9 (oleic acid) and C18:2n6 (linoleic acid) were the main fatty acids in the hepatopancreas of P. clarkii. 10,12,13 The hepatopancreas is the main organ for fat storage in crustaceans, and the changes in fatty acid content are closely related to the changes in fatty acid content during ovarian development. During the maturation process of ovaries, the content of certain fatty acids increases while the corresponding fatty acids decrease in the hepatopancreas (Amran et al, 2018).…”
Section: Effects Of Estradiol On the Content Of Fatty Acids In The He...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results are different from previous studies, which commonly found that C18:n9 (oleic acid) and C18:2n6 (linoleic acid) were the main fatty acids in the hepatopancreas of P. clarkii. 10,12,13 The hepatopancreas is the main organ for fat storage in crustaceans, and the changes in fatty acid content are closely related to the changes in fatty acid content during ovarian development. During the maturation process of ovaries, the content of certain fatty acids increases while the corresponding fatty acids decrease in the hepatopancreas (Amran et al, 2018).…”
Section: Effects Of Estradiol On the Content Of Fatty Acids In The He...mentioning
confidence: 99%
“…5,8,9 The type and content of fatty acids in the ovary of P. clarkii undergo significant changes during its development, which will naturally be reflected in the hepatopancreas, the main organ that provides nutrition for ovarian development. 10 Previous studies found that estradiol not only existed in the hepatopancreas of P. clarkii, but was also related to ovarian development. 10 Thus, this study aimed to investigate the effect of exogenous estradiol injection on the fatty acid content and tissue structure of the hepatopancreas of P. clarkii, to provide a reference for studying the roles of estradiol in ovarian development in crustaceans.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lecithin contains fatty acids, phosphate, and choline, which facilitate the metabolism of carbohydrates and lipids [ 14 ]. Phospholipids are involved in the structure of cell membranes and lipoproteins, which are needed for embryonic and larval growth and the luminal emulsification of lipids components [ 15 , 16 ]. Accordingly, lecithin can facilitate the absorption of lipids and digested nutrients through the intestines of fish [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%